Toxicity Study of Volatile Oil Boesenbergia pandurata (Roxb) Schlecht Rhizome to Larvacide of Aedes aegypti and GC-MS Profile - Widyasari Putranti; Saiful Bachri (Majalah Obat Tradisional, 2018)
Boesenbergia pandurata (Roxb) Schlecht has been recognized by society as traditional drug for a long time. The active constituent of this plants especially the volatile oil, which contains monoterpenes and sesquiterpenes. The use of Boesenbergia pandurata (Roxb) Schlecht rhizome which is a botanical insecticide shows higher safety because the molecule is easily broken down into harmless compounds against the environment. The aim of this research were to know about the activity of larvacide from the volatile oil of Boesenbergia pandurata (Roxb) Schlecht rhizome and also to analyze its chemical compounds using GC-MS. The volatile oil was isolated from Boesenbergia pandurata (Roxb) Schlecht with steam and water destillation method. The volatile oil in the aqueous ethanol 70 % v/v was made as the test solution for larvacide. The concentrations of the volatile oil of Boesenbergia pandurata (Roxb) Schlecht rhizomes used were 150 ppm; 201 ppm; 270 ppm; 362 ppm; 485 ppm; 650 ppm. Abate was used as positive control at concentration 0,001 ppm; 0,0025 ppm; 0,0065 ppm; 0,016 ppm; 0,04 ppm; 0,1 ppm while aqueous ethanol 70 % v/v was used as negative control. Each treatment were used 20 larvaes of Aedes aegypti and was observed during 24 hours. The data of died larvae were counted to estimate the values of LC50 with probit analysis method. The chemical compound of volatile oil of Boesenbergia pandurata (Roxb) Schlecht was analyzed by the GC-MS. The results of this research showed that the volatile oil of Boesenbergia pandurata (Roxb) Schlecht have clear-brass colour, bitter taste, typically aromatic, rendemen equal to (0,25 ± 0,011) % v/w and refractive index 1,4818. The value of LC50 for the volatile oil of Boesenbergia pandurata (Roxb) Schlecht rhizome is (407,06 ± 31,6985) ppm while abate equal to (0,0132 ± 0,0013) ppm. This matter indicates that abate more potent to larvae of Aedes aegypti. The result of analyze the component of the volatile oil of Boesenbergia pandurata (Roxb) Schlecht by the GC-MS obtained of 15 peak chromatogram and 6 peak which has identified showed the possibility the existence of champene, eucalyptol, ocimene, camphora, geraniol, methyl cinnamate.